Blast-1 possesses a glycosyl-phosphatidylinositol (GPI) membrane anchor, is related to LFA-3 and OX-45, and MAPS to chromosome 1q21-23 - Staunton, D; Fisher, R; LeBeau, M; Lawrence, J; Barton, D; Francke, U; Dustin, M; Thorley-Lawson, D (1989)
Blast-1 is a human activation-associated glycoprotein expressed on the surface of leukocytes. Analysis of a translated sequence from a Blast-1 cDNA reveals a single hydrophobic sequence which could traverse the plasma membrane, but is devoid of charged residues that might represent a cytoplasmic tail. Consistent with this characteristic, Blast-1 is demonstrated here to be anchored to the cell surface through a glycosyl-phosphatidylinositol (GPI)-containing lipid. Comparison of Blast-1 to other GPI-anchored membrane proteins revealed a striking primary and secondary structure similarity with MRC OX45 and the lymphocyte function antigen LFA-3. The degree of overall amino acid sequence homology reveals that OX45 is a rat homologue of Blast-1. The greatest homology to LFA-3 occurs between their NH2-terminal Ig-like domains. Evidence is presented that demonstrates that Blast-1 and LFA-3 possess a disulfide-bonded second domain. These common characteristics demonstrate a structural and evolutionary relationship between Blast-1, OX45, LFA-3, and CD2, which in turn suggests a functional role for Blast-1 in cell-cell interactions in the immune response. The gene for Blast-1 has been localized to chromosome 1 q21-q23, indistinguishable from the C12 cluster of Ig superfamily genes, raising the possibility that they may be linked.